Pemeriksaan Pajak Dan Tingkat Kepatuhan Wajib Pajak Badan Terhadap Penerimaan Pajak Studi Pada Wajib Pajak KPP Pandeglang - Eko Hadi Siswanto; Rachmi Septia Yustikasari (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2015)
The purpose of this research is to study it there is positive influence of tax audit and tax payer compliance of tax receipts.The research method used is causal, with the unit of analysis Entity Tax Payer. Sampling method used stratified random sampling.The tax audit and tax payer compliance of tax receipts by using the instruments measured questionnaire with likert scale. Source analysis performed by descriptive analysis and linear regression. The result shows that’s positive influence of influence of tax audit and negative influence tax payer compliance of tax receipts.